Low temperature debonding of toughened structural adhesive joints: A new approach to repairs in the automotive industry - Bartley, Aurélie; Chudalla, Nick; Meschut, Gerson; Wibbeke, Tim Michael (International Journal of Adhesion and Adhesives)

Material-Preserving Extrusion of Polyamide on a Twin-Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Schall, Christoph Wilhelm Theodor; Wanke, Sven; Kley, Marina (Polymers)

The Role of Design in interdisciplinary Product Development – Challenges, Research Approaches and Further Research needs - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In global competition, companies are continuously searching for a competitive advantage. A growing number of companies have identified the design of their products as a major success factor. The promises for companies associated with outstanding design are extremely attractive, ranging from better customer experience to higher sales growth. But even though the advantages of design seem to be compelling, companies are still having difficulties in leveraging the benefits of design. In this paper, we want to identify the underlying challenges that explain this gap. We are especially interested in the role and challenges of design in interdisciplinary product development. Therefore, we perform a literature review that clarifies terminology, analyses research approaches and identifies challenges. We determine seven key challenges for design in interdisciplinary product development. Furthermore, we observe a limited scope of research approaches in the reviewed literature. Based on these findings, we propose three further research directions to strengthen the role of design in interdisciplinary product development in the future.

Designing Business Models for a Circular Economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The megatrend sustainability will significantly change the future value creation of manufacturing companies. Their current linear value creation models need to change to conform to the requirements of sustainability. To face the challenges the circular economy has emerged as a promising economic model. With the shift from a linear to a circular economy, companies have to adjust their current business models. However, they still lack knowledge and adequate methods to develop circular business models. Hence, the aim of the paper is a circular business model canvas (CBMC) for designing circular businesses. A systematic literature review was conducted to identify significant criteria for circular business models. The criteria were analyzed utilizing a qualitative content analysis to derive the business model elements required for the circular economy. Existing elements from the Business Model Canvas were enriched and five new elements, e.g., reverse logistics, were found. Then, the business model elements were logically arranged resulting in the CBMC. It guides companies to systematically develop business models for the circular economy. The CBMC was evaluated by applying it within a mediumsized company in the electronics sector.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.

Privacy in the Age of Neurotechnology: Investigating Public Attitudes towards Brain Data Collection and Use - Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

Jesus heilt - warum nicht alle? - Kammeyer, Katharina; Neumann, Anna (Religion 5-10. Themen, Unterrichtsideen, Materialien)

Runtime Verification of Crypto APIs: An Empirical Study - Torres, Adriano; Costa, Pedro; Amaral, Luis; Pastro, Jonata; Bonifácio, Rodrigo; d'Amorim, Marcelo; Legunsen, Owolabi; Bodden, Eric; Dias Canedo, Edna (IEEE Transactions on Software Engineering)
Keywords: Software

Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Can the configuration of static analyses make resolving security vulnerabilities more effective? - A user study - Piskachev, Goran; Becker, Matthias; Bodden, Eric (Empirical Software Engineering)
Abstract The use of static analysis security testing (SAST) tools has been increasing in recent years. However, previous studies have shown that, when shipped to end users such as development or security teams, the findings of these tools are often unsatisfying. Users report high numbers of false positives or long analysis times, making the tools unusable in the daily workflow. To address this, SAST tool creators provide a wide range of configuration options, such as customization of rules through domain-specific languages or specification of the application-specific analysis scope. In this paper, we study the configuration space of selected existing SAST tools when used within the integrated development environment (IDE). We focus on the configuration options that impact three dimensions, for which a trade-off is unavoidable, i.e., precision, recall, and analysis runtime. We perform a between-subjects user study with 40 users from multiple development and security teams - to our knowledge, the largest population for this kind of user study in the software engineering community. The results show that users who configure SAST tools are more effective in resolving security vulnerabilities detected by the tools than those using the default configuration. Based on post-study interviews, we identify common strategies that users have while configuring the SAST tools to provide further insights for tool creators. Finally, an evaluation of the configuration options of two commercial SAST tools, Fortify and CheckMarx , reveals that a quarter of the users do not understand the configuration options provided. The configuration options that are found most useful relate to the analysis scope.
Keywords: Software

The connection of open science practices and the methodological approach of researchers - Steinhardt, Isabel; Bauer, Mareike; Wünsche, Hannes; Schimmler, Sonja (Quality & Quantity)
Abstract The Open Science movement is gaining tremendous popularity and tries to initiate changes in science, for example the sharing and reuse of data. The new requirements that come with Open Science poses researchers with several challenges. While most of these challenges have already been addressed in several studies, little attention has been paid so far to the underlying Open Science practices (OSP). An exploratory study was conducted focusing on the OSP relating to sharing and using data. 13 researchers from the Weizenbaum Institute were interviewed. The Weizenbaum Institute is an interdisciplinary research institute in Germany that was founded in 2017. To reconstruct OSP a grounded theory methodology (Strauss in Qualitative Analysis for Social Scientists, Cambridge University Press, Cambridge, 1987) was used and classified OSP into open production, open distribution and open consumption (Smith in Openness as social praxis. First Monday, 2017). The research shows that apart from the disciplinary background and research environment, the methodological approach and the type of research data play a major role in the context of OSP. The interviewees’ self-attributions related to the types of data they work with: qualitative, quantitative, social media and source code. With regard to the methodological approach and type of data, it was uncovered that uncertainties and missing knowledge, data protection, competitive disadvantages, vulnerability and costs are the main reasons for the lack of openness. The analyses further revealed that knowledge and established data infrastructures as well as competitive advantages act as drivers for openness. Because of the link between research data and OSP, the authors of this paper argue that in order to promote OSP, the methodological approach and the type of research data must also be considered.
Keywords: Open Science

Collective Minimum Contributions to Counteract the Ratchet Effect in the Voluntary Provision of Public Goods - Alt, Marius; Kesternich, Martin; Gallier, Carlo; Sturm, Bodo (Journal of Environmental Economics and Management)
We experimentally test a theoretically promising amendment to the ratchet-up mechanism of the Paris Agreement. The ratchet-up mechanism prescribes that parties’ commitments to the global response to climate change cannot decrease over time, and our results show that its effect is detrimental. We design a public goods game to study whether cooperation is promoted by an amendment to the mechanism that stipulates that all agents must contribute at least a collectively chosen minimum based on the principle of the lowest common denominator. We find that binding collective minimum contributions improve the effectiveness of the ratchet-up mechanism. Non-binding minimum contributions, by contrast, do not encourage cooperation. Our data indicate that the difference is attributable to conditional cooperative dynamics. If other participants contribute less than the collective minimum contribution, even initially cooperative participants start to negatively reciprocate this form of non-compliance by contributing less.
Keywords: global public goods; climate change; institutions; ratchet-up mechanism; minimum contributions; laboratory experiment

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Inter-Charity Competition under Spatial Differentiation: Sorting, Crowding, and Spillovers - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of Economic Behavior and Organization)

Strategische Planung des Einstiegs in die Plattformökonomie - Özcan, Leon; Drewel, Marvin; Koldewey, Christian; Dumitrescu, Roman (Schwerpunkt Business Model Innovation)

Soziale Eingebundenheit als Schlüssel?! - Perspektiven zur Förderung von student engagament in der Hochschullehre - Steinhardt, Isabel; Thielsch, Angelika (Aktive Teilhabe fördern. ICM und Student Engagement in der Hochschullehre)

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Hellweg, Talea Davina; Schneider, Martin; Rückert, Ulrich; Harteis, Christian; Pilz, Sarah (The Digital Twin of Human)
Today, it is possible to collect and connect large amounts of digital data from various sources and life domains. This chapter examines the potential and the risks of this development from an interdisciplinary perspective. It defines the ‘global digital twin’ of a human being as the sum of all digitally stored information and predictive knowledge about a person. It points out that, compared to the digital twin of a machine, the human global digital twin is far more complex because it comprises the genetic code and the biographic code of a person. The genetic code contains not only a simple ‘construction plan’ but also hereditary information, in a form that is difficult to read. The biographic code contains all other information that can be assembled about a person, which is obtained via data from cameras, microphones, or other sensors, as well as general personal information. When the growing wealth of information concerning the genetic code and the biographical code is properly utilised, insights from biology and the behavioural sciences may be used to predict personal events such as health problems, job resignations, or even crimes. Because our own interests and those of private firms are partly in conflict over the use of this powerful knowledge, it is still unclear whether the global digital twins of humans will become a liberating or disciplining force for citizens. On the one hand, human beings are not machines: They are aware of their digital twin and therefore are able to influence it throughout their lives. Because of their free will, human beings are in general difficult to predict. Dystopias of full control over individual behaviour are therefore unlikely to materialise. On the other hand, private firms are beginning to take advantage of the available digital twins of humans by monopolising data access and by commercialising predictive knowledge. This is problematic because, unlike machines, human beings cannot only benefit from but also suffer due to their digital twins as they attempt to shape their own lives. We illustrate these issues with some examples and arrive at two conclusions: It is in the public interest for people to be granted more property rights over their personal global digital twins, and publicly funded research needs to become more interdisciplinary, much like private firms that have already begun to perform interdisciplinary research.

Kollegiale Kooperation im Lehrer:innenberuf. - Kullmann, Harry (Beruf Lehrer:in. Ein Studienbuch (2. Auflage))

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

Hitting the Breaks While Working from Home. Changes in Taking-Breaks Behaviours During Pandemic Lockdowns - Voicu, Bogdan; Țălnar-Naghi, Dana; Neguț, Adriana; Glăvan, Eugen; Tufă, Laura; Florea, Alexandra (Sociológia - Slovak Sociological Review)
Keywords: Sociology and Political Science